1999
DOI: 10.1038/sj.bjp.0702656
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effector pathways regulate the insulin secretory response to the imidazoline RX871024 in isolated rat pancreatic islets

Abstract: 1 When isolated rat islets were cultured for 18 h prior to use, the putative imidazoline binding site ligand, RX871024 caused a dose-dependent increase in insulin secretion at both 6 mM and 20 mM glucose. By contrast, a second ligand, efaroxan, was ineective at 20 mM glucose whereas it did stimulate insulin secretion in response to 6 mM glucose. 2 Exposure of islets to RX871024 (50 mM) for 18 h, resulted in loss of responsiveness to this reagent upon subsequent re-exposure. However, islets that were unresponsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…When the membrane potential was measured using the perforated patch mode, efaroxan induced oscillatory patterns of depolarization in desensitized as well as in normal cultured ␤-cells (65). Measurements of [Ca 2ϩ ] c in single ␤-cells showed that at all three efaroxan concentrations tested (10,30, and 100 mol/l), the increase in efaroxan-desensitized ␤-cells was the same as in control-cultured ␤-cells (Fig. 6A).…”
Section: Desensitization By Depolarizing Insulin Secretagoguesmentioning
confidence: 99%
“…When the membrane potential was measured using the perforated patch mode, efaroxan induced oscillatory patterns of depolarization in desensitized as well as in normal cultured ␤-cells (65). Measurements of [Ca 2ϩ ] c in single ␤-cells showed that at all three efaroxan concentrations tested (10,30, and 100 mol/l), the increase in efaroxan-desensitized ␤-cells was the same as in control-cultured ␤-cells (Fig. 6A).…”
Section: Desensitization By Depolarizing Insulin Secretagoguesmentioning
confidence: 99%
“…However, despite this, KU14R does not stimulate insulin secretion from rat islets under any condition studied. Rather, it acts as a potent antagonist of the secretory response to efaroxan (2,13,(28)(29)(30). This suggests that KU14R may interact with two sites in the ␤-cell.…”
mentioning
confidence: 99%
“…For this work, we took advantage of the recent observation that a close structural analog of efaroxan, KU14R, acts as a functional antagonist of imidazoline-mediated responses in the pancreatic ␤-cell (2,13,(28)(29)(30). Previous studies have shown that, despite blocking K ATP channels, KU14R does not modify the rate of glucose-induced insulin secretion from rat islets (29,30).…”
Section: K Atp Channel-independent Effects Of Efaroxanmentioning
confidence: 99%
See 1 more Smart Citation
“…Idazoxan works only at very high concentration. Comparing Efaroxan with RX871024, the latter shows a lower activity at low glucose concentration in stimulating the secretion of insulin, but exhibits a higher activity at high glucose concentration; so RX871024 shows higher potential as an antidiabetic drug [28,29]. The order of the four imidazolines in stimulating the secretion of insulin and the inhibitory activity of K ATP channel is the same.…”
Section: The Relationship Of the Function And Binding Modementioning
confidence: 82%